2019
DOI: 10.1158/1078-0432.ccr-18-2572
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor D5 is a Modulator of Tumor Response to Dopamine Receptor D2 Antagonism

Abstract: Purpose: Dopamine receptor D2 (DRD2) is a G proteincoupled receptor antagonized by ONC201, an anticancer small molecule in clinical trials for high-grade gliomas and other malignancies. DRD5 is a dopamine receptor family member that opposes DRD2 signaling. We investigated the expression of these dopamine receptors in cancer and their influence on tumor cell sensitivity to ONC201. Experimental Design: The Cancer Genome Atlas was used to determine DRD2/DRD5 expression broadly across human cancers. Cell viability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…Interestingly, our proteomic analysis revealed depletion of several cell cycle proteins, which may explain a previously described cell cycle arrest phenotype caused by ONC201 (Kline et al 2016). We also did not recover HRI (EIF2AK1) or PKR (EIF2AK2) genes, or other mediators of the integrated stress response (Ishizawa et al 2016;Kline et al 2016), nor any dopaminergic receptors or other GPCR-related genes (Kline et al 2018;Madhukar et al 2019;Nii et al 2019;Prabhu et al 2019). Although it is possible that cell type-specific gene expression may explain the absence of these genetic hits, the most parsimonious explanation is that CLPP is the primary target of the imipridones.…”
Section: Genetic Specificity Of Imipridone Actionmentioning
confidence: 42%
See 1 more Smart Citation
“…Interestingly, our proteomic analysis revealed depletion of several cell cycle proteins, which may explain a previously described cell cycle arrest phenotype caused by ONC201 (Kline et al 2016). We also did not recover HRI (EIF2AK1) or PKR (EIF2AK2) genes, or other mediators of the integrated stress response (Ishizawa et al 2016;Kline et al 2016), nor any dopaminergic receptors or other GPCR-related genes (Kline et al 2018;Madhukar et al 2019;Nii et al 2019;Prabhu et al 2019). Although it is possible that cell type-specific gene expression may explain the absence of these genetic hits, the most parsimonious explanation is that CLPP is the primary target of the imipridones.…”
Section: Genetic Specificity Of Imipridone Actionmentioning
confidence: 42%
“…20 phase II clinical trials for hematological malignancies and solid tumors (Allen et al 2016). Several mechanisms of action have been ascribed to ONC201 and its more potent derivate ONC212 (Wagner et al 2017), including: FOXO3A-mediated induction of TRAIL (Allen et al 2013) upon inhibition of the prosurvival AKT/ERK pathway (Allen et al 2013); activation of the integrated stress response (ISR) via the eIF2a kinases HRI and PKR, resulting in ATF4/CHOP-mediated upregulation of the TRAIL DR5 receptor (Kline et al 2016); activation of the ISR independent of eIF2a (Ishizawa et al 2016); and antagonism of dopaminergic G protein-coupled receptors (GPCRs) or activation of other GPCRs (Kline et al 2018;Madhukar et al 2019;Nii et al 2019;Prabhu et al 2019). Cell biological characterization suggests that ONC201 disrupts mitochondrial function and that cancer cells that do not depend on mitochondrial respiration are ONC201-insensitive (Greer et al 2018).…”
mentioning
confidence: 99%
“…By contrast to antipsychotics that competitively antagonize DRD2, ONC201 does not antagonize other dopamine receptors or other GPCRs and is a more potent anti-tumor agent as compared to stronger DRD2 antagonists. Moreover, ONC201 exhibits a wide therapeutic index as compared to antipsychotics in tumor versus normal cell viability assays [26] . Schild analyses and radioligand competition assays revealed competitive and non-competitive DRD2 antagonism by ONC201 at concentrations that coincide with its anti-cancer activity.…”
Section: Onc201 Mechanism Of Actionmentioning
confidence: 99%
“…7a-b). The other direct target of ONC201 response, DRD2 [26][27][28] , did not predict ONC201 response in either our patient cohort or DepMap/PRISM glioma cell atlas. Further analysis of the pan-cancer cell line atlas demonstrated that ONC201 resistance correlates with: (i) EGFR expression, (ii) EGFR dependency and (iii) EGFR inhibitor (EGFRi) sensitivity (Fig.…”
Section: Mainmentioning
confidence: 86%
“…We next performed an analysis of human cancer cell lines from DepMap/PRISM 25 to assess correlation of FOXG1 and EGFR expression (and other reported predictive makers [26][27][28] ) with sensitivity to ONC201. CLPP expression was identi ed as the strongest predictor of ONC201 sensitivity at the pan-cancer level 29 .…”
Section: Mainmentioning
confidence: 99%